Carcass Traits and Value of Meat and Byproducts of Goat - Muthukumar, M.; Kandeepan, G.; Pathak, Vikas; Rathod, K. S.; Ambadkar, R. K.; Thomas, R.; Kulkarni, V.V. (Journal of Meat Science, 2019)
A study was conducted to collect data on carcass traits covering 1517 goats across India. The results indicated that the live weight and  dressed carcass weight of goats ranged from 12.54 to 28.16 kg and 5.84 to 13.41 kg, respectively with an average dressing percentage of  46.86%. There was a significant difference (P 15 to < 20 kg (Group 2), >20 to 15 to >20 kg (36.85 %). The overall average live weight of goats from Maharashtra (20.58 kg) and Andhra Pradesh  (19.51 kg) were higher when compared to other states. Except skin, all the byproducts are utilized for human consumption and the yield  of edible (blood, head, feet, stomach and intestine, heart, liver, lungs, kidney and fat) and inedible (skin) byproducts as percentage of live  goat weight were 43.79 and 9.35 %, respectively. In terms of commercial value of goat carcass, major revenue comes from meat (81.07  – 85.78%), followed by edible offal (11.55 – 16.47%) and skin (2.39 – 2.68%).
Keywords: Carcass traits; Carcass; Byproducts; Goat; Value